JENIS-JENIS KESEJAHTERAAN KARYAWAN - Bexi Aliyanto; Dedi Irawan; Moh. Subakti (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2024)
Welfare is the payment of salaries, remuneration, benefits, compensation,and various other gifts provided by the company to employees, whether inthe form of money, goods or other services that can provide satisfaction toemployees at work so that their life needs are met properly. Welfare goals:(1) To increase employee loyalty and engagement, (2) Provide peace andfulfill the needs of employees and their families, (3) Motivate work passion,discipline, and work productivity of employees, (4) Help the work toachieve goals smoothly, (5 ) Maintaining the health and quality ofemployees, (6) Improving the social status of employees and their families.Welfare benefits: (1) More effective labor recruitment, (2) Increased moraleand loyalty, (3) Better public relations, (4) Satisfaction of employee needs,(5) Reducing the threat of government intervention. The types of welfareare: (1) Economic welfare, for example, in the form of pension money, foodmoney, transportation money; (2) Welfare in the form of facilities, forexample, prayer rooms/mosques, cafeterias/canteens, sports, arts,cooperative and shop leave; (3) Welfare is of a service nature, for example:health center/doctor, employee pick-up, babysitting